1.2: Invited Paper: Dynamic threshold voltage compensation IGZO‐GOA circuit for AMOLED display. (4th October 2019) - Xue, Yan; Han, Bai-Xiang; Wang, Xian; Zhou, Shuai; Liao, Cong-Wei; Zhang, Sheng-Dong; Chaw, Gary; Lu, Po-Yen; Wu, Yuan-Chun
Abstract : A dual‐gate amorphous indium‐gallium‐zinc‐oxide (a‐IGZO) thin‐film transistor (TFT) has been proposed and designed in this work. Based on this specific structure, a technologically advanced external Vth compensation system, where Vth can be controllable by an external DC signal source, has been developed for gate driver on array (GOA). Subsequently, the working mode of this circuit was introduced. Moreover, detailed simulation has been performed to study the appropriate process window. Finally, the proposed GOA circuit exhibited stable high‐voltage output pulse, meanwhile, the lifetime showed an significant improvement with the utilization of the external Vth compensation system. It should be also mentioned that a wide pulse of 3.6ms has been obtained to sense Vth of driving TFTs in pixel circuits.